Policies for sustainable land management in the highlands of Tigray, Northern Ethiopia: summary of papers and proceedings of the conference held at the Axum Hotel, Mekelle, Ethiopia, March 28-29, 2002. - Gebremedhin, Berhanu; Pender, John L.; Ehui, Simeon; Haile, Mitiku (International Food Policy Research Institute, 2003)
Participants in this workshop reviewed and discussed findings from the research project‚ Policies for Sustainable Land Management in the Highlands of Tigray, Northern Ethiopia, begun in January 1998, and from other related research being conducted in the highlands of Tigray by Mekelle University and its collaborators.